Gifts of the Immigrants, Woes of the Natives: Lessons from the Age of Mass Migration - Tabellini, Marco (Review of Economic Studies, 2020)
In this article, I jointly investigate the political and the economic effects of immigration, and study the causes of anti-immigrant sentiments. I exploit exogenous variation in European immigration to U.S. cities between 1910 and 1930 induced by World War I and the Immigration Acts of the 1920s, and instrument immigrants’ location decision relying on pre-existing settlement patterns. I find that immigration triggered hostile political reactions, such as the election of more conservative legislators, higher support for anti-immigration legislation, and lower redistribution. Exploring the causes of natives’ backlash, I document that immigration increased natives’ employment, spurred industrial production, and did not generate losses even among natives working in highly exposed sectors. These findings suggest that opposition to immigration was unlikely to have economic roots. Instead, I provide evidence that natives’ political discontent was increasing in the cultural differences between immigrants and natives. Results in this article indicate that, even when diversity is economically beneficial, it may nonetheless be socially hard to manage.